Lead Chalcogenides: Discovering Electron‐Transfer‐Driven Changes in Chemical Bonding in Lead Chalcogenides (PbX, where X = Te, Se, S, O) (Adv. Mater. 49/2020). Issue 49 (8th December 2020) - Maier, Stefan; Steinberg, Simon; Cheng, Yudong; Schön, Carl‐Friedrich; Schumacher, Mathias; Mazzarello, Riccardo; Golub, Pavlo; Nelson, Ryky; Cojocaru‐Mirédin, Oana; Raty, Jean‐Yves; Wuttig, Matthias
Abstract : In article number 2005533, Matthias Wuttig and co‐workers study systematic changes of chemical bonding in lead chalcogenides (PbX, where X = Te, Se, S, O) to comprehend their properties. They discover an electron‐transfer‐driven transition from highly anharmonic, metavalent bonding in thermoelectric PbX (X = Te, Se, S) to iono‐covalent bonding in β‐PbO, highlighting the relevance of the concept of metavalent bonding for materials design.